COMPILATION OF SUCCESSFUL FRGS 2021 PROPOSALS - Suraya Hani Adnan,; Nafarizal Nayan,; Anuar Raze Abd Rahim, (2024)
The publication of ‘Compilation of Successful FRGS 2021 Proposals’ serves the essential purpose of guiding readers through the context in which their research proposals will be evaluated. It provides insights into the expectations of reviewers and the evaluation panel, shedding light on what influences the funding policy and budget allocation, particularly concerning research output. This resource is invaluable for academics, researchers, and postgraduate students seeking to craft compelling grant applications and research proposals. Within this book, you will find fourteen research proposals that encompass a wide range of multidisciplinary and interdisciplinary research areas, all of which received funding from the Malaysian government. These proposals serve as exemplars of high-quality research proposals, offering clear and engaging writing. Each proposal is extensively annotated, providing a user friendly guide that makes it easy for readers to understand and follow the rules and guidelines for effective proposal writing. Additionally, ‘Compilation of Successful FRGS 2021 Proposals’ offers a concise explanation of how to address key elements, such as project background, knowledge domain, and the significance of the research issues at hand. It educates researchers on the critical factors involved in the journey from developing a scientific idea to successfully crafting a research proposal.